Growth and flowering of colored cotton cultivated in soils of distincts ESP and sheep manure - DA SILVA, EVANDRO MANOEL; NOBRE, REGINALDO GOMES; Barbosa, Joicy Lima; GHEYI, HANS RAJ; DA SILVA, FRANCISCO ALVES; BONIFÁCIO, BENEDITO FERREIRA (Comunicata Scientiae, 2019)
The inadequate management of irrigation has promoted the increase in the area of degraded soils through salinization and/or sodification, especially in irrigated perimeters of the northeastern semiarid, promoting environmental impacts and decrease in crop yield. In this manner, studies that aim to evaluate the tolerance of crops to salts, and/or techniques that minimize the deleterious effects of salt stress are highly viable. Based on this, the present study aimed to evaluate the influence of sheep manure doses over growth and flowering of the colored cotton cv. BRS Topázio, cultivated in soils with different exchangeable sodium percentages. A randomized block design was adopted, in a 5 x 4 factorial scheme, corresponding to the treatments of five exchangeable sodium percentages – ESP: 8.84, 12.55, 18.80, 28.80 and 38.80% and four sheep manure doses: 0, 5, 10 and 15% based on the volume of the soil, with 3 replications. At 90 days after sowing, it could be verified that the increment in the sheep manure doses added to the soil mitigated the negative effect of the ESP over the production of flower buds, beside stimulating plant growth, flower production and reducing the rate of flower abortion, independently of the ESP. The cotton cv. BRS Topázio is tolerant to soil ESP up to 38.8%, and anthesis is anticipated by the increase in exchangeable sodium.